1998
DOI: 10.1046/j.1365-2494.1998.5320146.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allowed grazing time, inert rumen bulk and length of starvation before grazing on the weight, composition and dermentative end‐products of the rumen contents of lactating dairy cows

Abstract: The effect of length of the allowed grazing time (Experiment 1), length of starvation time and placement in the rumen of inert bulk material before grazing (Experiment 2) on liquid and particulate rumen pool sizes, composition and fermentability was investigated. In Experiment 1, four lengths of allowed grazing time (1.00, 1.75, 2.50 and 3.25 h) after overnight starvation were compared. The allowed grazing time had no significant effect on total and liquid rumen pool sizes after grazing but did affect (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Assuming that at meal termination, ruminants would have reached maximal rumen capacity is misleading as well. This assumption is supported by Taweel et al [12] and Chilibroste et al [16] who reported findings where maximal rumen capacity had not been reached when grazing dairy cows terminated feeding bouts. Greenhalgh and Reid [17] reported similar results where sheep fed on hay and straw-terminated feed intake way before maximal gut capacity was reached.…”
Section: Introductionmentioning
confidence: 67%
“…Assuming that at meal termination, ruminants would have reached maximal rumen capacity is misleading as well. This assumption is supported by Taweel et al [12] and Chilibroste et al [16] who reported findings where maximal rumen capacity had not been reached when grazing dairy cows terminated feeding bouts. Greenhalgh and Reid [17] reported similar results where sheep fed on hay and straw-terminated feed intake way before maximal gut capacity was reached.…”
Section: Introductionmentioning
confidence: 67%
“…hydrolysis and fermentation, is very fast [37]. This hypothesis of a delay in the availability of the more rapidly fermentable substrates with animals fed fresh herbage has been supported by Chilibroste et al [7] who observed a very slow increase of the pool of ruminal volatile fatty acids when animals started to graze.…”
Section: Introductionmentioning
confidence: 80%
“…Rumen pH was measured immediately after sampling (pH electrode HI 1230, Hanna Instruments B.V., Ijsselstein, the Netherlands). After rumen pH measurement, a subsample of rumen fluid was taken, acidified with phosphoric acid, and stored at −20°C pending SCFA analyses by GC (GC-type Fisons HRGC MEGA2, Milan, Italy) as described by Chilibroste et al (1998). Milk production was recorded daily.…”
Section: Measurement and Samplingmentioning
confidence: 99%